Analysis The Factors Affecting The Use English of Week in The Islamic Boarding School Environment; Social Phenomena at Baitul Arqom Islamic Boarding School Jember - Vera Setyawati, Anik; Mukarromah, Inayatul; Qomariyah, Dewi Nurul (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
The use of English in Islamic boarding schools has become a crucial aspect of contemporary language education, as these schools aim to combine religious teachings with global communication skills. In this framework, English learning is interwoven with moral and spiritual values, shaping students who are both proficient in the language and ethically responsible. One key initiative is the English Week Program (EWP), which provides an immersive environment for practicing English. Despite this, students often struggle to maintain consistent use of English due to linguistic, psychological, and environmental barriers. This study explored the factors hindering the EWP at Baitul Arqom Islamic Boarding School, Balung, Jember, and examined strategies to improve students’ English practice. Employing a qualitative descriptive method, data were gathered through observations, interviews, and documentation involving six English coordinators and ten female students. Analysis was conducted through data reduction, display, and conclusion drawing, with validity ensured via source and technique triangulation. Findings identified obstacles such as limited vocabulary, pronunciation difficulties, low confidence, fear of errors, dominance of Arabic, insufficient exposure to English, inconsistent supervision, few mentors, and a punitive system causing psychological stress. Recommended strategies included structured weekly activities, role modeling by teachers and senior students, integration of moral and linguistic lessons, supportive monitoring, positive reinforcement, and diary-writing exercises to enhance engagement in both spoken and written English.